1997
DOI: 10.1006/jmla.1996.2500
|View full text |Cite
|
Sign up to set email alerts
|

A Destressing “Deafness” in French?

Abstract: Spanish but not French uses accent to contrast between words (e.g., tópo vs topó). Two populations of subjects were tested on the same materials to determine whether this difference has an impact on the perceptual capacities of listeners. In Experiment 1, using an ABX paradigm, we found that French subjects had significantly more difficulties than Spanish subjects to perform an ABX classification task based on accent. In Experiment 2, we found that Spanish subjects were unable to ignore irrelevant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
385
2
19

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(435 citation statements)
references
References 35 publications
29
385
2
19
Order By: Relevance
“…More generally, research has shown that listeners are attuned to the properties of the speech signal which are most relevant for their language (e.g., Otake et al, 1993Otake et al, , 1996Dupoux et al, 1997). Data exist that show that this tuning actually takes place very early, in the first year of life (see Kuhl, 1994;Werker, 1994 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, research has shown that listeners are attuned to the properties of the speech signal which are most relevant for their language (e.g., Otake et al, 1993Otake et al, , 1996Dupoux et al, 1997). Data exist that show that this tuning actually takes place very early, in the first year of life (see Kuhl, 1994;Werker, 1994 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Non-native suprasegmental contrasts, like non-native segmental contrasts, can present listeners with perceptual di$culty. Thus, stress contrasts in nonsense words are di$cult for French speakers to perceive, but easy for Spanish speakers (Dupoux, Pallier, SebastiaH n-GalleH s & Mehler, 1997); Spanish is a stress language, French is not. Perception of tone in Chinese is in#u-enced for English speakers by their knowledge of pitch patterns in English (Broselow, Hurtig & Ringen, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the perception of suprasegmental distinctions have revealed processing di!erences between native and non-native listeners. Thus as Dupoux et al (1997) showed, Spanish and French listeners di!er in how accurately they can perceive stress contrasts in nonsense words spoken by a Dutch speaker; similarly, Dutch and Finnish listeners can use suprasegmental correlates of stress as a cue to word onset, while French listeners do not (Vroomen, Tuomainen & de Gelder, 1998). While the discrimination of tone contrasts is a!ected by word}nonword status only for native listeners and not for non-native listeners (Fox & Unkefer, 1985;Cutler & Chen, 1997), overall similarity in discriminability of tone contrasts for native and non-native listeners (Burnham, Kirkwood, Luksaneeyanawin & Pansottee, 1992;Cutler & Chen, 1997) can mask processing di!erences * for instance, greater interdependence of segmental and suprasegmental judgments for tone language speakers than for speakers of non-tone languages (Repp & Lin, 1990;Lee & Nusbaum, 1993), or dependence on native distinctions in making the non-native distinctions (Broselow et al, 1987;Nishinuma et al, 1996).…”
mentioning
confidence: 99%
“…Such an interpretation is endorsed by findings that short-term memory is involved in stress assignment in non-brain damaged participants. Dupoux, Pallier, Sebastian, and Mehler (1997) reported a memory overload on performance in a study on stress 'deafness' in French non-brain-damaged participants. Spanish, but not French uses lexical stress to distinguish between minimal stress pairs of words (e.g.…”
Section: Discussionmentioning
confidence: 99%